Teachers' Strategies in Improving Students' Understanding of Aqidah and Akhlak at MI Az-Zahro - Eni Lionike; Indah Witriani; Muhammad Fadli; Tiara Nurhayati (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
Faith and morals education plays an important role in shaping the religious character of students in elementary schools. In the context of MI Az-Zahro Pagaralam, the values ​​of Islamic faith and morality are not only taught theoretically but also internalized through role modeling, habituation, and emotional and spiritual approaches. This study aims to examine the strategies teachers use to improve students' understanding of faith and morality and evaluate their effectiveness. The research method employs a qualitative case study approach, incorporating observation, interviews, and documentation techniques. The results showed that exemplary behavior, habituation of worship, storytelling method, and active collaboration with parents are the main strategies in fostering student character. Despite facing challenges such as the influence of digital media and limited facilities, teachers continue to innovate to strengthen faith and character education. The findings are expected to be a reference for the development of Islamic character education in madrasah ibtidaiyah.   Keywords: Faith Education, Moral Education, Religious Character, Madrasah, Learning Strategy, Basic Education.